Randomized controlled pilot study: effect of carrageenan emulsifier on inflammation and gastrointestinal symptoms in quiescent ulcerative colitis - Reijo Laatikainen; Markku Lehto; Noora Mäkelä-Salmi; Markku Hillilä; Per-Henrik Groop; Hanne Salmenkari (Food & Nutrition Research, 2023)
Background: Animal models have provided some evidence of the pro-inflammatory effects of the commonly used emulsifier carrageenan. However, the effects of food-grade carrageenan among people with ulcerative colitis (UC) are largely unknown. Methods: A randomized, placebo-controlled cross-over study comparing high molecular carrageenan and oat-based beta-glucan preparation (placebo) among patients (n = 7) with quiescent UC was performed. Primary endpoint was Simple Clinical Colitis Activity Index (SCCAI) at the end of the treatment (7th day). Secondary analyses included biochemical biomarkers of inflammation, intestinal permeability, detoxification of intestinal lipopolysaccharide (LPS), and gastrointestinal symptoms measured by visual analog scale. Results: There were no statistically significant differences in SCCAI or any biochemical markers between carrageenan and placebo periods, nor were there any significant differences when comparing either period to baseline. Gastrointestinal symptoms were higher during the placebo period; the sum of all symptoms and borborygmi was statistically significantly higher at the end of the placebo period than at the end of the carrageenan period (20.8 ± 18.6 vs. 13.3 ± 16.4; P = 0.031, and 29.7 ± 28.6 vs. 17.9 ± 23.6; P = 0.016). Conclusions: Our study suggests that at least short-term usage of food-grade carrageenan is safe among people with UC, but given the limitations of the current study, robust human studies are still urgently needed.